Design and simulations for a Penning Ion Trap Source for the CHIP-TRAP Mass Spectrometer. Issue 1 (1st April 2022) - Horana Gamage, M.; Bhandari, R.; Gamage, N. D.; Keblbeck, D.; Redshaw, M.
Abstract: At Central Michigan University (CMU) we have been developing the CMU High Precision Penning Trap (CHIP-TRAP) mass spectrometer for precise mass measurements on stable and long-lived radioactive isotopes. As part of this apparatus, we have designed a Penning Ion Trap (PIT) source to produce singly-charged, low intensity (∼100s to 1000s of ions in ∼1 μ s duration) ion pulses from gaseous samples. The PIT source is similar to a PIG type source, composed of an electric field superimposed on a magnetic field. The electric field is produced by a cylindrical Penning trap structure consisting of two end caps and a center ring with a trap volume of about 0.8 cm 3 . The trap structure is housed inside a permanent neodymium ring magnet bore. Gas is inserted into the trapping region and ionized by an ∼1 μ A electron beam from a thermal emitter. Ions are extracted from the PIT source by lowering the voltage on one of the end caps. They are then accelerated into the beam line. In this paper, we report on the design of the PIT source and simulations to investigate and characterize the expected beam properties.